The Influence of Burnout Level and Work Environment on Employee Engagement and Nurse Performance at Nene Mallomo Hospital Sidrap Regency - IHSAN RIFKI FAISAL, (Study of Scientific and Behavioral Management, 2024)
This research aims to determine the influence of Burnout level and Work Environment on Employee Engagement and performance of nurses at Nene Mallomo Hospital, Sidrap Regency, both directly and indirectly. The type of research carried out was quantitative research with a saturated sampling method which resulted in 110 respondents. Data was collected through distributing questionnaires and processed using statistical techniques such as classical assumption tests, path analysis, and multiple linear regression analysis. The research results show that burnout has a negative and significant effect on employee engagement, work environment has a positive and significant effect on employee engagement, burnout has a negative and insignificant effect on performance, work environment has a positive and significant effect on performance, employee engagement has a positive and significant effect on performance, employee engagement mediates the effect of burnout on performance, and mediates the effect of work environment on performance.